2018
DOI: 10.1002/1873-3468.13190
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural insights into an allelic variant causing the lysosomal storage disorder – aspartylglucosaminuria

Abstract: Glycosylasparaginase or aspartylglucosaminidase, EC3.5.1.26.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 37 publications
(91 reference statements)
1
22
0
Order By: Relevance
“…In contrast, a Flavobacterium system has become an excellent model system for these studies. The justifications to use the bacterial model include the following: (a) the Favobacterial GA shares the same αββα fold with the human enzyme; (b) Favobacterial and human GAs have a high sequence homology with an expect value of 1e‐48 in BLAST; (c) both enzymes utilize the same autoproteolytic process to cleave single‐chain precursors into mature amidases that allow glycoasparagine digestion; (d) although different in glycosylations, these two enzymes have an essentially identical 3D structure; (e) all the amino acids around the catalytic center, those within 4 Å of the bound substrate NAcGlc‐Asn, are 100% identical between these two homologs; (f) the bacterial homolog allows production of crystallographic amount and purity of AGU model enzymes to determine three‐dimensional structures and study their detailed kinetic parameters . Overall, these facts advocate suitability of using the Flavobacterium homolog to study the effects of AGU mutations on GA catalytic activities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, a Flavobacterium system has become an excellent model system for these studies. The justifications to use the bacterial model include the following: (a) the Favobacterial GA shares the same αββα fold with the human enzyme; (b) Favobacterial and human GAs have a high sequence homology with an expect value of 1e‐48 in BLAST; (c) both enzymes utilize the same autoproteolytic process to cleave single‐chain precursors into mature amidases that allow glycoasparagine digestion; (d) although different in glycosylations, these two enzymes have an essentially identical 3D structure; (e) all the amino acids around the catalytic center, those within 4 Å of the bound substrate NAcGlc‐Asn, are 100% identical between these two homologs; (f) the bacterial homolog allows production of crystallographic amount and purity of AGU model enzymes to determine three‐dimensional structures and study their detailed kinetic parameters . Overall, these facts advocate suitability of using the Flavobacterium homolog to study the effects of AGU mutations on GA catalytic activities.…”
Section: Resultsmentioning
confidence: 99%
“…The first one corresponds to the Canadian G203D variant . The second model structure corresponds to the Finnish T234I variant . These structural studies revealed that the Canadian variant appears to cause local conformational change outside of the amidase substrate site, which in turn disrupts the requisite autoprocessing step, thus persisting as a metabolically nonfunctional precursor protein .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations